Maxillary Sinus Osteoma: Case Report - Gözde Orhan Kubat; Caner Şahin; Özkan Özen (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Osteoma in maxillary sinus region is a benign osteoblastic lesion that can be observed very rarely in literature. When osteoma get big enough, it may cause obstruction in maxillary sinus ostium, compression symptoms at surrounding structures; if osteoma is small, it can be asymptomatic. The lesion may be followed if the case is asymptomatic, or treatment with surgery is done if the case is symptomatic or when a complication is occurred. We presented an osteoma in the maxillary sinus osteoma in the light of existing literature here in.